Elasticity and the Dialectic Tensions of Organizational Identity: How Can We Hold Together While We Are Pulling Apart? - Kreiner, Glen E.; Hollensbe, Elaine; Sheep, Mathew L.; Smith, Brett R.; Kataria, Niyati (Academy of Management Journal, 2015)
Given the ever-changing nature of contemporary workplaces, members often renegotiate how they view the identity of their organization. One way they do so is by expanding or contracting their conception of organizational identity. In studying these processes, we develop the construct of “identity elasticity”—the tensions that simultaneously stretch, while holding together, social constructions of identity. To explicate the parameters of elasticity, we problematize previous conceptions of the three foundations of organizational identity—centrality, endurance, and distinctiveness—and document the dialectic tensions experienced in their social constructions. We show how identity is experienced not only through a listing of attributes but also by negotiating a set of processual tensions. In so doing, we also bring together two competing views on organizational identity—process and characteristic. We show how experiencing and navigating the tensions of elasticity is a type of organizational identity work (process) that changes organizational members’ constructions of identity (characteristic). We develop our findings as a result of a 10-year-long multiple-method study of an organization undergoing significant growing pains in its identity—the Episcopal Church. Further, we position elasticity as a crucial construct with implications for how organizational identity is viewed.